Vaccine safety surveillance in pregnancy in low- and middle-income countries using GAIA case definitions: A feasibility assessment. Issue 45 (29th October 2018) - Stuurman, Anke L.; Riera, Margarita; Lamprianou, Smaragda; Perez-Vilar, Silvia; Anderson, Steven A.; Mangtani, Punam; Devlieger, Hugo; Verstraeten, Thomas; Zuber, Patrick L.F.; Guillard Maure, Christine
Abstract: Background: Global efforts to adequately monitor safety of new vaccines for pregnant women in low and middle-income countries (LMICs) are needed. The Global Alignment of Immunization Safety Assessment in pregnancy (GAIA) project recently published case definitions based on levels of diagnostic certainty for pregnancy- and neonatal outcomes and maternal vaccination. As a preliminary step to assessing the applicability of these definitions in LMICs, WHO selected sites and conducted a feasibility assessment to evaluate their ability to identify and classify selected outcomes (preterm birth, neonatal death, neonatal invasive bloodstream infection (NI-BSI), stillbirth) and maternal vaccination. Methods: Candidate sites were initially screened using a questionnaire. For each outcome, eligible sites were asked to retrospectively identify and collect information for three individuals born in 2016. Subsequently, outcomes were classified by level of diagnostic certainty. Results: Fifty-one sites (15 countries) were screened; 32 of them (9 countries) participated in the assessment and identified 315 subjects with the outcomes of interest. Twenty-four sites (8 countries) identified at least one subject per outcome and agreed to continue participating. The majority (80%) of preterm births, neonatal deaths, and NI-BSI subjects, but only 50% of stillbirths, could be assessed for diagnostic certainty. The main reasons for not classifying stillbirths were insufficient information to distinguish between antepartum and intrapartum stillbirth (29%); or that not all data for one subject fit into a single level of diagnostic certainty (35%). Forty-nine percent of mothers were considered vaccinated, 6% not-vaccinated, and vaccination status could not be assessed in 44% of them. Discussion: GAIA case definitions for four neonatal outcomes and maternal vaccination were successfully piloted in 24 sentinel sites across four WHO regions. Our assessment found that modification of the stillbirth definition could help avoid potential misclassification. Vaccine safety monitoring in LMICs will benefit from systematic recording of all vaccinations during pregnancy.